User authentication based on the three-stage keyboarding model - A. R. Abzalov; I. I. Kashapov; A. Yu. Orlov; I. R. Mamleev (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Objective. The article offers a three-stage model that allows increasing the effectiveness of authentication in the implementation of distance learning systems, not only in automatic proctoring systems but also in complex information systems of critical objects. Methods. Increasing the effectiveness of user authentication is achieved by increasing the accuracy of authentication using keyboarding. Results. The proposed model will help to implement the process of access differentiation for fraudsters and legal users, by adapting to the slightest changes in the keyboarding parameters, which allows increasing the authentication accuracy. During testing, one of the tested users was authenticated using a deviation comparison, while the other three users were authenticated using the χ2 criterion. The remaining users were not able to complete the authentication procedure at all stages of the system. Conclusion. The results of an experimental study showed the high ability of the proposed model of access control for legitimate users and attackers with some minor changes in the parameters of the keystrokes dynamics, improving the accuracy of user authentication. The user authentication reliability in practice was 97.5%.